1995
DOI: 10.1016/0014-5793(95)00393-n
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of a novel actin‐binding protein, p57, with a WD repeat and a leucine zipper motif

Abstract: A 57 kDa protein (p57) was obtained during the study on phosphatidylinositol-specific phospholipase C. Its cDNA was isolated from calf spleen and human leukemia cell line HL60 libraries and cloned. In the primary structures of p57, they have two unique amino acid sequence motifs, a WD repeat and a leucine zipper motif. Furthermore, p57 shared sequence similarity (40%) with coronin, an actin-binding protein responsible for chemotaxis, cell motility, and cytokinesis of Dictyostelium discoideum, which has only th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
101
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(102 citation statements)
references
References 19 publications
1
101
0
Order By: Relevance
“…The level of the ClipinC mRNA was extremely high in the brain, moderate in heart and ovary, and very low or undetectable in the other tissues examined in this study. As previously reported (12), the ClipinA transcript was mainly detected only in immune system tissues, i.e. spleen, thymus, and peripheral leukocytes.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The level of the ClipinC mRNA was extremely high in the brain, moderate in heart and ovary, and very low or undetectable in the other tissues examined in this study. As previously reported (12), the ClipinA transcript was mainly detected only in immune system tissues, i.e. spleen, thymus, and peripheral leukocytes.…”
Section: Resultssupporting
confidence: 84%
“…Analysis of the FC96 protein sequence with a protein data base disclosed an overall similarity to the Dictyostelium coronin (38.5%) and its mammalian homologs, i.e. p57 (43.9%) (12) and IR10 (61.0%) (13). An amino-terminal domain containing five WD repeats and a succeeding domain covering about 100 amino acids with a tendency to form an ␣-helical structure were well conserved among these molecules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed description was made in this study for three zebrafish homologues, coro1a, nephrosin, and dab2, that exhibited specific expression in hematopoietic͞ vascular tissues, but whose functions in mammals are poorly understood. Although there is currently no functional data on human CORO1A, mouse Coro1A has been shown to contain a WD (trp͞asp) repeat and a leucine zipper motif (26) and to reside on phagosomal membranes in cells infected by mycobacteria, thus preventing endocytic transport of these bacteria to lysosomes and promoting their intracellular survival in cultured macrophages (27). This observation is consistent with our results that coro1a is expressed in myeloid cells coexpressing mpo and indicates that coro1a is a marker for mature granulocyte and monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…All seven proteins are characterized by the presence of evolutionally conserved structural domains that include tryptophan/aspartic acid repeats that are implicated in the association with actin filaments. We previously identified p57/coronin-1 as the first mammalian coronin and found that this protein was selectively expressed in immune cells (9). We have also reported that p57/coronin-1 possesses at least two actin binding regions (10) and forms a homodimer via a leucine zipper motif present in the C-terminal coiled-coil region (11).…”
mentioning
confidence: 99%